Strateški cilji razvoja Beograjske metropolitanske regije v okviru evropskega prostorskega razvoja - Stojkov, Borislav (Urbani izziv, 2004)
In the last decade the importance of Belgrade has for known reasons seriosly deteriorated. For future development under the new circumstances it is therefore necessary to define several primary strategic goals. In this articlethe most important ones are presented, namely: new definition and positioning of the metropolitan region in relation to the European, macro-regional and regional hinterland or its position and role/function in the framework of Europe and the Balkans; establishment of efficient and sustainable transport infrastructure and adequate inclusion in the European transport system; deconcentrated concentration and restructuring; improving and placing economic structures for increasing economic competitiveness of themetropolitan region; protection and improving natural givings, cultural specifics and strengthening the metropolitan identity, as well as profiling the Belgrade metropolitan region with specialised economic activities, especially service activities oriented towards south-eastern Europe.
Keywords: Belgrade; Beograd; prostorski razvoj; razvojna strategija; urbani razvoj; urbanistično planiranje